Resposta tecidual em ratos submetidos à injeção submucosa de dois materiais de preenchimento com finalidade estética : análises clínica e histológica - Moure, Sabrina Pozatti (2011)
Dermal fillers are injectable products commonly used in aesthetic medicine with the intention of alleviating face wrinkles and increasing lip volume. This type of treatment, which often replaces traditional surgical procedures such as rhytidectomies, provides satisfactory cosmetic results. It is known, however, that there is a risk of undesired effects at the site of injection of the product or even at a distance. Dental literature reports numerous cases of orofacial injuries caused by the use of dermal fillers, reflecting a new reality in dental surgeons' practice. In this research, 2 of the most commonly used materials for aesthetic purposes by dermatologists and plastic surgeons were injected in rat tongues: 10% polymethylmethacrylate (n=16) and 20mg/mL hyaluronic acid (n=18), compared to an inert solution for control (n=16). After 7, 60 and 90 days, local clinical and histological alterations of each product were analyzed. The following factors were verified: intensity of the inflammatory response in the injection area (hematoxylin and eosin), the amount of newly formed blood vessels and macrophages (immunohistochemistry) and the density of collagen fibers (picrosirius).At the same experimental times, systemic migration of injected substances was observed through microscopic examination of organs of metabolism and excretion (liver and kidney) stained by hematoxylin and eosin. Results showed that both filling materials triggered some kind of local inflammatory response to a greater or lesser degree. In the comparative analysis, it was found that polymethylmethacrylate showed cases of foreign body reaction, while hyaluronic acid demonstrated characteristics suggesting biocompatibility. This research is part of a set of experiments related to the use of facial dermal fillers for aesthetic purposes and it reinforces the need for dental surgeons to identify and manage adverse reactions which may result from such currently widely used treatment.